KAJIAN KELAYAKAN PENERIMA MANFAAT (GAKIN PKH) TERHADAP PROGRAM BANTUAN PEMERINTAH DI KOTA SEMARANG - Tsabit Azinar Ahmad; Nana Kariada Tri Martuti; Satya Budi Nugraha; Amidi Amidi; Wahid Akhsin Budi Nur Sidiq (Badan Perencanaan Pembangunan Daerah Kota Semarang, 2019)
The Family of Hope Program (PKH) is one of the poverty alleviation programs organized by the Indonesian Ministry of Social Affairs. This conditional social assistance program aims to reduce the burden of spending and increase the income of poor and vulnerable families. Currently the number of PKH Beneficiary Families (KPM) reaches 25,593 households. In order to make improvements to the PKH program, it is necessary to evaluate the sustainability of the program's usefulness in the future. Therefore this research was conducted to evaluate the feasibility of beneficiary families of government assistance programs (KPM PKH) in Semarang City. Besides aiming to evaluate the suitability of the community / family of beneficiaries (KPM PKH) in Semarang City based on criteria set by the Government, this study also aims to analyze the distribution of the use / utilization of government assistance by KPM PKH in Semarang City. Feasibility Study of Beneficiary Family Benefit Program (KPM PKH) Against Government Assistance Program in Semarang City is carried out using a concurrent mixed strategy. In this strategy the researcher took qualitative and quantitative data at once in a certain time span. The results showed that the district with the highest number of recipients was Semarang Utara District. Meanwhile, Tugu District is the region with the lowest number of beneficiary families. The gradual selection and verification process makes PKH acceptance in Semarang City selectively and on target (fulfilling eligibility criteria).